Pengelolaan Madrasah Swasta dengan Sistem Patrimonial (Studi Komparasi Yayasan Miftahul Ma’arif Kaliwungu Kudus dengan Yayasan Manafi’ul Ulum Getassrabi Gebog Kudus) - Mohammad Hamdan (Southeast Asian Journal of Islamic Education Management, 2020)
Foundation (Yayasan) has vital roles in improving the education, particularly in Islamic schools (madrasah) which are mostly private schools. This study focused on the foundation roles and functions in improving the quality of education in Islamic schools (madrasah). Research aimed to study the foundation roles of Yayasan Darul Irfan, in Sawangan, Depok in managing its school, particularly in achieving the National Education Standard (Standar Pendidikan Nasional, SNP). This research, which used qualitative approach, also aimed to study the foundation functions, especially the school management organized by the foundation. The informants in this research were the foundation supervisor (Pembina Yayasan) and inspector (Pengawas Yayasan), the foundation board (Pengurus Yayasan), the headmaster, the vice-headmaster, the teachers, and the Head of Administration (Kepala Tata Usaha) of Yayasan Miftahul Ma’aarif Kaliwungu and Yayasan Manafiul Ulum Getassrabi Gebog. Data were analyzed by using qualitative and descriptive methods. Research results found that Yayasan Miftahul Ma’aarif Kaliwungu and Yayasan Manafiul Ulum Getassrabi Gebog has shown the education roles in the average level, although it has still not achieved the maximum level. In organizing the education of Yayasan Miftahul Ma’aarif Kaliwungu and Yayasan Manafiul Ulum Getassrabi Gebog according to eight National Education Standards, the Foundation shows more vital roles in finance management, Human Resources (SDM) management, and infrastructure management. The Foundation management has been carried out, particularly in Human Resources management, management development for the headmaster and head of administration. The Foundation also assisted in solving the issues, either amongst the individuals or the units/foundations. The Foundation has possessed specific mechanism in resolving the conflicts.